Which compound-earcon's attributes may improve a player's performance in a search-oriented gameplay: rhythm vs timbre? - Savvateev, Anton (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2018)
Earcons are commonly used by sound designers in order to support visual cues in a game andto make a gaming experience more enjoyable. This study covers two earcons’ attributes: rhythm and timbre. Rhythm and timbre attributes were chosen according to the earcon sounddesign guidelines from the previous studies. An experiment in a form of a video game was conducted in order to research whether one of the conditions can increase a players’performance. A subject had to choose the correct key to the door in order to go to the next location. There were 3 different locations and there were totally 5 different own-designed earcons: 1 incorrect earcon in the both conditions and 2 different correct earcons in each condition. 20 subjects with various gaming experience from the Luleå University of Technology participated in the experiment. The subjects were randomly divided into two groups with different conditions: rhythm and timbre. The amount of wrong trials and completion time were analyzed for each condition and the results were given with the help of Mann-Whitney U-test and t-test calculations. The results of U-test showed that there was a significant difference between two groups in terms of the wrong trials amount. Group with rhythm condition showed better performance in terms of the wrong trials amount. The t-test showed a significant difference between the two groups in terms of completion time. Group with timbre condition showed better timing performance, although considering the analysis it did not increase their performance in terms of making correct choices. Further research might be recommended on comparing various earcon attributes in different ecologically valid scenarios.